The Influence of Self-Image and Social Media Tiktok Brand Image on Korean-Style Fashion Purchasing Decisions on Gen Z in Kalapanunggal - Fitriyani Fitriyani; Yuli Novitasari; Riani Winarni (Priviet Social Sciences Journal, 2026)
The rise of social media platforms, particularly TikTok, has significantly impacted Generation Z’s consumption patterns, especially in the Korean-themed fashion sector. This study aimed to evaluate the individual and collective influences of TikTok, self-perception, and brand image on the purchase choices of Korean-style clothing among Generation Z residents of Kalapanunggal Subdistrict. Using an associative quantitative methodology, data were collected through a questionnaire from 100 respondents. The analytical framework involved assessing the validity and reliability. Empirical findings indicate that TikTok usage significantly and positively influences purchasing behavior, with a t-value of 3.755 (p < 0.001). Similarly, self-image showed a substantial positive correlation with a t-value of 2.090 (p = 0.039), and brand image emerged as the primary determinant with a t-value of 3.892 (p < 0.001). Collectively, these three variables significantly influenced purchasing decisions, as evidenced by an F-statistic of 121.629 (p < 0.001). Furthermore, the adjusted R-squared value of 0.785 indicates that 78.5% of the variance in consumer decisions can be attributed to the examined predictors, while the remaining 21.5% is influenced by external variables beyond this study’s scope.